Impact of the development of acute kidney injury on patients admitted to the pediatric intensive care unit, - Ferreira,Marina Catuta de Rezende (2020)
Abstract Objective: To identify the risk factors for the development of acute kidney injury and for short and long-term mortality of patients with acute kidney injury after admission to the Pediatric Intensive Care Unit. Materials and methods: Retrospective analysis of patients admitted to the Pediatric Intensive Care Unit from January 2004 to December 2008. Acute kidney injury was defined by the KDIGO criterion. Risk factors for acute kidney injury, in-hospital, and long-term mortality were obtained through multivariate logistic regression analysis. Long-term mortality (up to 2011) was obtained by searching the institution's database and by telephone contact with patients' family members. Results: A total of 434 patients were evaluated and the incidence of acute kidney injury was 64%. Most acute kidney injury episodes (78%) occurred within the first 24hours after admission to the Pediatric Intensive Care Unit. The risk factors for the development of acute kidney injury were: low volume of diuresis, younger age, mechanical ventilation, vasoactive drugs, diuretics, and amphotericin. Lower weight, positive fluid balance, acute kidney injury, dopamine use and mechanical ventilation were independent risk factors for in-hospital mortality. Long-term mortality was 17.8%. Systolic blood pressure, PRISM score, low volume of diuresis, and mechanical ventilation were independent risk factors associated with long-term mortality after admission to the Pediatric Intensive Care Unit. Conclusion: Acute kidney injury was a frequent, early event, and was associated with in-hospital mortality and long-term mortality after admission to the Pediatric Intensive Care Unit.